I think you may be looking at this the wrong way.
There are three distinct logical rules which are all equivalent. Each rule holds for all propositions $P$ and $Q$.
Rule 1: $\neg \neg P \implies P$
This is the classic "proof by contradiction" rule.
Rule 2: $(\neg P \implies \neg Q) \implies (Q \implies P)$
This is "proof by contrapositive".
Rule 3: $P \lor \neg P$
This is the so-called "law of excluded middle" (a name which I don't like, but that's another story).
Each of these logical rules can be proved using the others (and the other rules of constructive logic, also known as intuitionist logic).
(2) $\to$ (1): Take $Q$ to be true. Then $\neg P \implies \neg Q$ is the statement that $\neg P$ implies false, which is the same as saying $\neg \neg P$. Conversely, saying $Q \implies P$ is the same as saying that true implies $P$, which is equivalent to $P$. So $(\neg P \implies \neg Q) \implies (Q \implies P)$ is equivalent to $\neg \neg P \implies P$.
(3) $\to$ (2): Suppose $\neg P \implies \neg Q$. Suppose $Q$. Now we have $P \lor \neg P$. In the case that $P$ is true, we have $P$. And in the case that $\neg P$ holds, we have $\neg Q$, which contradicts $Q$. This proves that $(\neg P \implies \neg Q) \implies (Q \implies P)$.
(1) $\to$ (3): We first prove the statement $\neg \neg (P \lor \neg P)$. Suppose that $\neg (P \lor \neg P)$. Now suppose $P$. Then $P \lor \neg P$. But this contradicts $\neg (P \lor \neg P)$. Therefore, $\neg P$. Then $P \lor \neg P$. But this contradicts $\neg (P \lor \neg P)$. Therefore, $\neg \neg (P \lor \neg P)$.
We now apply proof by contradiction to conclude that $\neg \neg (P \lor \neg P) \implies P \lor \neg P$, and we therefore conclude that $P \lor \neg P$.
So the moral of the story here is that any proof which is done using any one of these three rules can always be rephrased to use another of the 3 rules. In particular, any proof using rule 1 can always be rephrased to use only rule 2.
There is another way to look at this which illustrates why it almost always seems more natural to you to use proof by contrapositive as opposed to proof by contradiction.
Consider the fact that whenever we're proving just about any fact whatsoever, we're proving this fact in the context of some assumptions that we've made.
For example, suppose I know that $x$ is a positive real number, and I wish to prove $\exists y \in \mathbb{R} (y \cdot x = 1)$. Then one can also view this as proving the implication $(x > 0) \implies \exists y \in \mathbb{R} (y \cdot x = 1)$.
In particular, let's suppose we've made an assumption $Q$, and then we have proved $\neg \neg P$ on our way to proving $P$ by contradiction.
Then we can also view this proof as a proof of $Q \implies \neg \neg P$. This is equivalent to proving $\neg (Q \land \neg P)$, which is in turn equivalent to proving that $\neg P \implies \neg Q$.
So our proof, in the context of $Q$, that $\neg \neg P$ holds can also be viewed as a proof of $\neg P \implies \neg Q$.
From there, we wish to conclude, in the context of the assumption $Q$, that $P$ holds. That is, we wish to conclude $Q \implies P$.
So in fact, what we're "really doing" is proving $\neg P \implies \neg Q$ and then concluding from this fact that $Q \implies P$.
So in this sense, all proofs by contradiction with any assumptions whatsoever are actually proofs by contrapositive. We collect all the assumptions into a single proposition $Q$, prove $\neg P \implies \neg Q$, and then conclude that $Q \implies P$.
This illustrates the fact that proof by contradiction is really just proof by contrapositive where no assumptions are made. Of course, making no assumptions is equivalent to only assuming $\top$. Put another way, proof by contradiction is just proof by contrapositive in the case where $Q = \top$. And this is indeed exactly how we proof that proof by contradiction is a valid technique using proof by contrapositive (exactly (2) $\to$ (1) above).